2006
DOI: 10.1126/science.1128326
|View full text |Cite
|
Sign up to set email alerts
|

Plant Genotypic Diversity Predicts Community Structure and Governs an Ecosystem Process

Abstract: Theory predicts, and recent empirical studies have shown, that the diversity of plant species determines the diversity of associated herbivores and mediates ecosystem processes, such as aboveground net primary productivity (ANPP). However, an often-overlooked component of plant diversity, namely population genotypic diversity, may also have wide-ranging effects on community structure and ecosystem processes. We showed experimentally that increasing population genotypic diversity in a dominant old-field plant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

43
893
12
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 766 publications
(978 citation statements)
references
References 19 publications
43
893
12
8
Order By: Relevance
“…[1 ,2-8,9 ]). Studies have found that plant diversity positively influences arthropod diversity and abundance [3,4,8,10], and alters plant-arthropod and arthropod-arthropod interactions [3,7,11,12]. These findings emphasize that conserving and manipulating plant diversity in natural and managed systems, respectively, is crucial for maintaining ecosystem function [13][14][15].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…[1 ,2-8,9 ]). Studies have found that plant diversity positively influences arthropod diversity and abundance [3,4,8,10], and alters plant-arthropod and arthropod-arthropod interactions [3,7,11,12]. These findings emphasize that conserving and manipulating plant diversity in natural and managed systems, respectively, is crucial for maintaining ecosystem function [13][14][15].…”
Section: Introductionmentioning
confidence: 94%
“…For example, diversity may cause changes in plant traits which arise from aboveground and belowground interactions among neighbouring plants [4][5][6], or due to increased habitat heterogeneity affecting consumer foraging behaviour ( [38,39], i.e. effects of trait diversity).…”
Section: Effects Of Plant Diversity On Plant-insect Herbivore and Hermentioning
confidence: 99%
See 2 more Smart Citations
“…Ecologists increasingly recognize the value of understanding evolutionary as well as ecological factors underlying community dynamics [4][5][6][7][8][9][10][11][12]. Evolutionary differentiation has been shown to alter pairwise species interactions [13], communities [14][15][16][17] and ecosystems [16,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%